Competition amongst Eph receptors regulates contact inhibition of locomotion and invasiveness in prostate cancer cells - Astin, Jonathan W.; Batson, Jennifer; Kadir, Shereen; Charlet, Jessica; Persad, Raj A.; Gillatt, David; Oxley, Jon D.; Nobes, Catherine D. (Nature cell biology, 2010)
Normal migrating cells exhibit contact inhibition of locomotion (CIL) when meeting a neighbouring cell, but metastatic cancer cells lose this inhibition. Interactions btween ephrin and ephrin receptors are now shown to underlie CIL in migrating cells. Metastatic cancer cells typically fail to halt migration on contact with non-cancer cells. This invasiveness is in contrast to normal mesenchymal cells that retract on contact with another cell. Why cancer cells are defective in contact inhibition of locomotion is not understood. Here, we analyse the dynamics of prostate cancer cell lines co-cultured with fibroblasts, and demonstrate that a combinatorial code of Eph receptor activation dictates whether cell migration will be contact inhibited. The unimpeded migration of metastatic PC-3 cells towards fibroblasts is dependent on activation of EphB3 and EphB4 by ephrin-B2, which we show activates Cdc42 and cell migration. Knockdown of EphB3 and EphB4 restores contact inhibition of locomotion to PC-3 cells. Conversely, homotypic collisions between two cancer cells results in contact inhibition of locomotion, mediated by EphA–Rho–Rho kinase (ROCK) signalling. Thus, the migration of cancer cells can switch from restrained to invasive, depending on the Eph-receptor profile of the cancer cell and the reciprocal ephrin ligands expressed by neighbouring cells.